Perceptions and determinants of eating for health and performance in high-level male adolescent Rugby Union players - Stokes, E. G.; Hughes, R.; Shaw, D. M.; O`Connor, H. T.; Beck, K. L. (Sports, 2018)
Sports nutrition recommendations provide guidance on dietary strategies to optimise sports performance. However, research indicates that young athletes often find it difficult to follow these guidelines in practice. Limited research exists on the determinants that influence adherence to sports nutrition guidelines. This study aimed to explore the perceptions and determinants of eating for health and performance in high-level male adolescent rugby union players. Determinants were explored using semi-structured individual interviews in New Zealand high-level male rugby union players (n = 20, 16-18 years). Interviews were recorded, transcribed, and then underwent thematic analysis. Perceptions of eating for health and performance included balance and variety, appropriate portions, and specific foods. Both adolescent- and sport-specific determinants influenced the food choices of participants. Determinants relevant to adolescent lifestyles included the influence of significant others such as peers and family but also included the taste, cost, convenience, and availability of food. Sports-specific determinants revolved around the desire to enhance sports performance, motivation to perform, and team culture. The media (mainstream and social media), physical appearance, and feeling good were identified as both adolescent- and sport-specific factors influencing food choice. These findings highlight the importance of having support and positive role modelling to help young athletes make optimal food choices for health and performance. Strategies to further enable healthy eating practices should aim to strengthen the support available to young athletes in the home, school, and sporting environments and should include education on appropriate social media use to inform eating for health and performance.